We live in a virtual world: Training the trainee using an integrated visual reality simulator curriculum. (8th April 2022) - Mooney, Samantha S.; Hiscock, Richard J.; Hicks, Lauren; Narula, Shagun; Maher, Peter J.; Readman, Emma; Pendlebury, Adam; Ellett, Lenore
Abstract : Background: Gynaecology trainees struggle to obtain adequate procedural experience. Training programs integrating virtual reality simulators (VRS) have been suggested as a solution. Aims: The study aimed to assess if a VRS training program (LapSim ®, Surgical Sciences, Göteborg, 2017) improved live operating performance at six months for novice and experienced trainees. Additional outcomes included the association between LapSim ® logged time and live operating performance at six months, LapSim ® scores and live operating performance at zero and sixmonths and the difference in benefit for novice and experienced gynaecology trainees. Methods: A prospective intervention study was conducted. Novice and experienced trainees were enrolled, and comparisons made at zero‐ and six‐month time points. The intervention groups were provided with a laparoscopic gynaecology curriculum incorporating VRS. Controls underwent routine training only. Assessment of live operating performance was conducted after six months training. Results: Thirty‐five trainees participated, and 25 had access to the VRS curriculum (17 novice and eight experienced trainees). Access to the VRS curriculum and time spent training on the LapSim ® made no difference to live operating ability for either intervention group ( P > 0.05). The median (interquartile range) hours of VRS usage were 7.9 (4.5–10.8) and 6.0 (4.0–6.8) for novice and experienced trainees respectively. The intervention group provided positive feedback on the utility of VRS in their laparoscopic skill development. Conclusion: Optimal utilisation of VRS in Australian training paradigms remains incompletely understood. Further research is required to establish the most effective integration of VRS into training models to ensure uptake and transferability to the operating theatre.